PENGARUH INDIKATOR ENTOMOLOGI DAN STATUS RESISTENSI Cypermethrin NYAMUK Aedes sp TERHADAP Incidence Rate CHIKUNGUNYA DI KECAMATAN TAWANGSARI KABUPATEN SUKOHARJO - , Erna Handayani; , dr. Tri Baskoro Tunggul Satoto, MSc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : There were 639 cases with clinical symptoms of Chikungunya at 2013 in Sukoharjo. Subdistrict Tawangsari has highest incidence rate of Chikungunya 183/100.000 people from the total population. There are 8 villages with Chikungunya. It is necessary to research about how big the effect of indicators covering entomology (house index, container index, breteau index, ovitrap index). Cypermethrine status resistance also needs to be investigated because Sukoharjo District use active ingredient cypermethrine for 5 years. Objective : Determine the effect of entomology indicator and cypermethrine resistance status of Aedes sp against Chikungunya incidence rate in the subdistrict Tawangsari Sukoharjo. Determine clustering cases of Chikungunya. Methods: The study is an observational analytic study is conducted with a cross-sectional study design. Samples are taken by purposive sampling technique. Sampling sites in 8 villages of cases. The independent variable is indicator of entomology (house index, breteau index, ovitrap index, container index) and cypermethrine resistance status of Aedes sp. The Incidence rate is the dependent variable. Statistical analysis to test the indicators entomology using linear regression, whereas to test the resistance status using the Spearman rank test. Results : Results of linear regression analysis showed, there is effect of house index, container index, breteau index against incidence rate with p value of 0.000 (p < 0.05), whereas no effect on ovitrap index against incidence rate with p value 0.135 (p > 0,05). The percentage contribution variables effect of entomologists indicator (house index, container index, breteau index, ovitrap index) is 92.5% (R square = 0.925). Aedes aegypti mosquitoes already resistant status, whereas Aedes albopictus still a tolerant and susceptible. There is no significant effect the resistance status of Aedes albopictus against the incidence rate (p = 0.162), Aedes aegypti resistance status is not effect the incidence rate because has constant returns is resistance. Using GPS and mapping results are analyzed using SaTscan show Chikungunya cases in subdistrict Tawangsari to form clusters. Conclusion : There is effect of house index, container index, breteau index against the incidence rate, while ovitrap index no effect on incidence rate. There is no significant effect between the resistance status of the incidence rate of Aedes sp. Chikungunya cases grouped to form clusters.